Hubungan Antara Tipe Kepemimpinan Kepala Sekolah dengan Semangat Kerja Guru di UPT SMP Negeri 7 Kota Mojokerto Tahun Pelajaran 2016/2017 - Muhammad Muhajir (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
The effectiveness of PBM can be determined by the number of factors ranging from climate, infrastructure, human resources and so forth. But people tend to think that the effectiveness of PBM is more determined by the learning climate. Even for capitalists the quality of PBm is more determined by the availability of educational facilities. The objectives of this study are: 1) To find out the leadership model applied by the Head of SMP Negeri 7 Kota Mojokerto.2) To find out the teacher's work spirit in SMP Negeri 7 Kota Mojokerto.3) To find out how far the relationship between the Principal's leadership model and morale teacher at SMP Negeri 7 Kota Mojokerto. This study uses quantitative research with analysis of product moment from Pearson and simple linear regression. The population in this study were 55 people and all of them were used as research samples, so that they were called saturated samples. From the results of the analysis it was concluded that: 1) The leadership model applied by the Head of Mojokerto City Middle School 7 was very good with an average score of 95.09%. 2) The work spirit of teachers in SMP Negeri 7 Kota Mojokerto is very high with an average of 94.36%. 3) There is a strong relationship between the Principal Type of School Leadership and Teacher's Spirit of Work in the 7th grade of Mojokerto City 2011/20112 Academic Year with the regression equation Y = - 7,471 X + 0.428 K + ? and based on the test of the leadership of the headmaster teacher work is 62.8% while the remaining 37.2% is influenced by other factors